Harvey Washington Wiley papers - Wiley, Harvey Washington, 1844-1930.
Correspondence, memoranda, diaries, speeches, lectures, writings, legal records, clippings, printed matter, maps, blueprints, graphs, tables, photographs, and other papers relating to Wiley's life and career as a chemist. Documents his years as student and educator; chief of the U.S. Bureau of Chemistry (1883-1912) lecturer on the Chautauqua circuit; and head of the Bureau of Food, Sanitation, and Health of the Good Housekeeping Institute (New York, N.Y.). Includes material pertaining to his work which culminated in passage of the U.S. Food and Drugs Act (1906).
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Chemist, educator, lecturer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Bureau of Chemistry; United States; Good Housekeeping Institute (New York, N.Y.). -- Bureau of Food, Sanitation, and Health; Chautauquas -- United States; Drugs -- Law and legislation -- United States; Food adulteration and inspection -- United States; Food law and legislation -- United States; Authors; Chemists; Educators; Lecturers